Syariah Financial Literacy Among SME Owner In Padang City - Silvy Astari; Howardi Vizha Adha; Engla Sulistia (Publikasiku, 2023)
Financial literacy is basic skill that should be have by human being. Syariah Financial literacy is based on Islamic perspective different with conventional financial literacy. Padang Panjang city is known as Serambi Makah, most of the population in the city have Islam as their religion. This paper distinguish the understanding of SME owner regarding syariah financial literacy. We found that the small medium enterprise owner in Padang Panjang City high financial behaviour and financial attitude but low syariah financial knowledge.